A Case Report of Takayasu’s Arteritis and Ulcerative Colitis in a Pediatric Patient with Chronic Recurrent Multifocal Osteomyelitis Successfully Treated with Infliximab: Diagnostic Clues in Disease Associations and Immune Dysregulation - Viveka Clare De Guerra; Humaira Hashmi; Bree Kramer; Rula Balluz; Mary Beth Son; Deborah Stein; Alicia Lieberman; Mahmoud Zahra; Rabheh Abdul-Aziz (Case Reports in Rheumatology, 2019)
Background. Takayasu’s arteritis with comorbid chronic recurrent multifocal osteomyelitis and ulcerative colitis is rare in the pediatric population. Treatment with anti-TNF alpha agents such as infliximab has been a successful treatment strategy in adults and can be used effectively in the pediatric population. Case Presentation. We present the case of a 15-year-old Caucasian girl with a history of chronic recurrent multifocal osteomyelitis and ulcerative colitis presenting with hypertensive emergency secondary to Takayasu’s arteritis with middle aortic syndrome. She was treated with corticosteroids and methotrexate and ultimately required infliximab infusions of 15 mg/kg every 4 weeks to successfully control her symptoms and normalize her inflammatory markers. Conclusions. In this case, we discuss the use of infliximab in an adolescent patient with chronic recurrent multifocal osteomyelitis, ulcerative colitis, and Takayasu’s arteritis. The significance of this case is determined by the unique occurrence of all three conditions in a pediatric patient, the important consideration of vasculitis in the differential of a pediatric patient presenting with hypertensive emergency, the need for vigilance for detecting diagnostic clues, signs, and symptoms, knowledge of disease associations when evaluating a patient with a predisposition for autoinflammatory conditions, and the use of increasing doses of infliximab to control symptoms.